Patterns and Predictors of Disclosure of Sexual Orientation to Healthcare Providers among Lesbians, Gay Men, and Bisexuals - Durso, Laura E. (2012)
The present study sought to identify patterns and predictors of disclosure of sexual orientation to healthcare providers among lesbian, gay, and bisexual (LGB) adults. METHODS: Respondents were 396 self-identified LGB individuals ages 18–59, recruited from diverse community venues in New York City, with equal numbers of men and women and Whites, Blacks, and Latinos. Respondents were interviewed at baseline and 1-year follow-up. We assessed the relationships among disclosure of sexual orientation, demographic characteristics, health, and minority stress. RESULTS: Rates of nondisclosure to healthcare providers were significantly higher among bisexual men (39.3%) and bisexual women (32.6%) compared with gay men (10%) and lesbians (12.9%). Bivariate and multivariate logistic regression models predicting disclosure of sexual orientation indicated that patient age, level of education, immigration status, medical history, level of internalized homophobia, and degree of connectedness to the LGB community were significant factors, along with sexual identity. Nondisclosure of sexual orientation was related to poorer psychological wellbeing at one year follow-up. CONCLUSION: Our findings suggest that interventions targeting sexual minorities ought to carefully tailor messages to subpopulations. In particular, interventionists and clinicians ought to be mindful of differences between bisexually- and gay/lesbian-identified individuals.